Innovation Trends in Cross border E-commerce Logistics Models - Han, Fang (Journal of Theory and Practice of Management Science, 2024)
With the rapid development of social and economic level, the strength of urban construction is increasing day by day, which puts forward strict requirements for the development of logistics mode. According to the current actual situation, cross-border e- commerce logistics mode has gradually been widely used, which fundamentally avoids the occurrence of previous problems and will also bring new opportunities and challenges to the development of e-commerce. In order to quickly promote the development of cross-border e- commerce logistics mode, it is necessary to carefully analyze its current development status according to the actual situation and enhance the development progress of cross-border e-commerce logistics mode. Based on this, the research focuses on the innovation and development trend of cross-border e-commerce logistics mode.